Metabolite Profiling of Ebony (Diospyros celebica Bakh) Leaves and Wood Extracts Using LC-MS/MS - Dien Atin Boritnaban; Alfi Hudatul Karomah; Dewi Anggraini Septaningsih; Muhammad Majiidu; Fifi Gus Dwiyanti; Iskandar Zulkarnaen Siregar; Mohamad Rafi (Indonesian Journal of Chemistry, 2022)
Ebony (Diospyros celebica Bakh) is an endemic forest tree species found in Sulawesi whose basic information on its metabolite profile is still lacking. The objective of this research was to separate and identify putatively metabolite present in the leaves and wood of ebony across Sulawesi. Separation and identification of ebony metabolites were carried out using UHPLC-Q-Orbitrap HRMS analysis. Using ultrasonication with ethanol as the extracting solvent, we used powdered ebony leaves and wood. The results showed that the metabolites contained in the leaves and wood of ebony were 59 metabolites. About 14 compounds were found in the leaves and wood, 21 compounds in the wood, and 24 compounds in the leaves. The identified metabolites are flavonoids, terpenoids, amino aldehydes, alkaloids, quinones, steroids, amino acids, fatty acids, and saccharides. Clustering of ebony using principal component analysis obtained leaves and wood groups using peak area of known compounds as the variable.